Demographics, Psychological Resilience, and Coping Mechanisms of Non-Officer Policemen in Distant Assignments: A Mixed-Method Study - Nitollano, Ryan Vargas (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the psychological resilience and coping mechanisms of non-officer policemen assigned to distant deployments within the Police Regional Office Bangsamoro Autonomous Region (PRO BAR). Grounded in stress appraisal theory, resilience theory, and person–environment fit theory, the research utilized an explanatory sequential mixed-methods design. Quantitative data were collected from 151 non-officer policemen selected through purposive sampling from 247 eligible personnel. Standardized instruments measured resilience and coping, and statistical analyses included descriptive statistics, multivariate analysis of variance, non-parametric tests, and Spearman’s rank-order correlation. A qualitative phase involving ten participants with moderate to high resilience levels employed inductive thematic analysis to explore lived experiences. Findings revealed generally moderate resilience across demographic groups, with problem-focused coping emerging as the dominant strategy. A weak, marginal positive association was observed between resilience and problem-focused coping, while no significant relationships were found between resilience and emotion-focused or avoidant coping. Significant differences in coping were identified across age, marital status, and years of service, but not by sex or rank. Qualitative themes highlighted cultural adaptation, sustained family communication, emotional maturity, and strengthened professional commitment as central to resilience, reflecting Filipino values of unity, empathy, and shared identity. The study concludes that resilience among non-officer policemen is a socially and organizationally supported process shaped by institutional structures and cultural foundations. It recommends strengthening psychological services, institutionalizing resilience-building and coping enhancement programs, enhancing family connectivity initiatives, and integrating comprehensive workplace mental health systems within the PNP. This study aligns with SDG 3 (Good Health and Well-Being), SDG 8 (Decent Work and Economic Growth), and SDG 16 (Peace, Justice, and Strong Institutions) by promoting mental health, improving working conditions, and reinforcing institutional effectiveness in law enforcement. Its sustainability impact lies in supporting institutional resilience, workforce stability, and governance effectiveness in geographically and politically complex regions such as BARMM.